2016
DOI: 10.1177/0734242x16661053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different pre-treatment methods for the removal of limonene in citrus waste and their effect on methane potential and methane production rate

Abstract: . Assessment of different pre-treatment methods for the removal of limonene in citrus waste and their effect on methane potential and methane production rate. Waste Management and Research, 34(12) AbstractThe objective of this study was to assess the limonene removal efficiency of three pre-treatment methods when applied to citrus waste and to evaluate their effects on the biochemical methane potential (BMP) and the methane production rate (MPR) using batch anaerobic tests. The methods tested were based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Essential oil, such as patchouli oil, also proved as reduce methane production [108]. Removal of D-limonene has been studied with the aim of improving methane production [106,[109][110][111]. One of the studies applied solvent pretreatment using hexane to reduce the D-limonene content in orange peel.…”
Section: The Substrate-related Issues For Optimum Vfas Productionmentioning
confidence: 99%
“…Essential oil, such as patchouli oil, also proved as reduce methane production [108]. Removal of D-limonene has been studied with the aim of improving methane production [106,[109][110][111]. One of the studies applied solvent pretreatment using hexane to reduce the D-limonene content in orange peel.…”
Section: The Substrate-related Issues For Optimum Vfas Productionmentioning
confidence: 99%
“…In fact, EOs obtained through steam distillation can be easily degraded because of the instability of terpene hydrocarbons. Conversely, Ruiz et al . showed that solvent extraction, compared with steam distillation, was the most efficient method for limonene recovery from orange peel.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods are commonly used for the extraction of EOs, including steam distillation and solvent extraction. Steam distillation is generally used on an industrial scale, especially for d ‐limonene recovery . Unfortunately, besides the low EO removal, the elevated temperature and the long extraction time could modify the volatile molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a competitive advantage over methanogens for electrons which result in inhibition of methanogenesis. Ruiz et al (2016) evaluated the effect of three different types of pretreatment (biological pretreatment by fungi, steam distillation and ethanol extraction) on biogas production of citrus waste. Limonene removal efficiency of biological pretreatment, steam distillation and ethanol extraction were 22%, 44% and 100%, respectively.…”
mentioning
confidence: 99%